Getting a Grip on the Adhesion Mechanism of Epiphytic Orchids – Evidence From Histology and Cryo-Scanning Electron Microscopy - Tay, Jessica Y. L.; Zotz, Gerhard; Gorb, Stanislav N.; Einzmann, Helena J. R. (Frontiers in Forests and Global Change, 2021)
Plants and animals evolve different attachment structures and strategies for reversible or permanent adhesion to different substrate types. For vascular epiphytes, having the ability permanently attach to their host plants is essential for establishment and survival. Unlike mistletoe roots, roots of vascular epiphytes do not penetrate the host tissues but instead achieve attachment by growing in close contact to the surface of the substrate. However, the fundamental understanding of the attachment functions of epiphytic roots remains scarce, where majority of studies focused on the general root morphology, their functional properties and the descriptions of associated microbial endophytes. To date, research on attachment strategies in plants is almost entirely limited to climbers. Therefore, this study aims to fill the knowledge gap and elucidate the attachment functions of roots of epiphytic orchids. With the use of histology and high-resolution cryo-SEM technique with freeze fracturing, the intimate root-bark substrate interface of epiphytic orchid Epidendrum nocturnum Jacq was investigated. Results showed a flattened underside of the root upon contact with the substrate surface, and the velamen layer appeared to behave like a soft foam, closely following the contours of the substrate. Root hairs emerged from the outermost velamen layer and entered into the crevices in the substrate, whenever possible. A layer of amorphous substance (glue-like substance) was observed on the surface of the root hairs. Combining the observations from this study and knowledge from previous studies, we hypothesised that epiphytic orchid roots produced a layer of glue-like substance to adhere the root to the substrate. Then root hairs are produced and enter into the voids and crevices of the substrate. This further generates a mechanical interlocking mechanism between root and substrate, thus reinforcing the attachment of the root (and hence the whole plant) to its substrate.